(untitled) (International Journal of Physiotherapy, 2016)
Background: Physiotherapists have an occupationally elevated risk of dermatoses. One aim of skin care seminars for specific professional groupsin individual prevention programme in Germany is to ensure appropriate use of safety measures during patient treatment. Initially physiotherapists often think skeptically about the use of gloves and patients’ acceptance of this protective measure. So the objective of this study was to assess the practicality of glove use during physiotherapy (qualitative investigation) and customer acceptance of them during massage (quantitative investigation). Methods: Structured problem-focused interviews about glove usage were held with 20 skin diseased physiotherapists and masseurs after skin care seminars. The data was evaluated inductively using Mayring’s qualitative content analysis. The clients’ acceptance was tested in a controlled randomized three setting study with 120 subjects who received a back massage and evaluated quality aspects of their massage in a questionnaire. The physiotherapist was wearing either gloves of PVC, gloves made of nitrile rubber or no gloves at all. A non-inferiority test was used to test group differences. Result: The majority of participating physiotherapists considered the use of protective gloves a practical and useful measure. However, occasional problems in everyday practice and in special therapy methods were reported. The analysis of 120 questionnaires (100% response rate) for quality aspects and the willingness to pay regarding client acceptancein a massage - with or without gloves -showed a non-inferiority result for massages with gloves. Conclusion: Convincing individual physiotherapists of the benefits of wearing gloves is crucial for implementation of this preventive measure. It is improbable that patients would refuse services because therapists wear gloves during treatments. Consequently, the usage of gloves is unlikely to result in a loss of practice custom.